2017
DOI: 10.1098/rspb.2017.1710
|View full text |Cite
|
Sign up to set email alerts
|

The effect of climate change on the duration of avian breeding seasons: a meta-analysis

Abstract: Many bird species are advancing the timing of their egg-laying in response to a warming climate. Little is known, however, of whether this advancement affects the respective length of the breeding seasons. A meta-analysis of 65 long-term studies of 54 species from the Northern Hemisphere has revealed that within the last 45 years an average population has lengthened the season by 1.4 days per decade, which was independent from changes in mean laying dates. Multi-brooded birds have prolonged their seasons by 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(111 citation statements)
references
References 62 publications
6
90
6
1
Order By: Relevance
“…Therefore, we regard the occurrence of these second broods in most cases not as a best‐of‐a‐bad‐job strategy after producing poorly during the first breeding attempt. Indeed, the three Dutch second broods in produced 13 fledglings, of which one (male) recruit was observed as breeder in (average first year recruitment rate is 4%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, we regard the occurrence of these second broods in most cases not as a best‐of‐a‐bad‐job strategy after producing poorly during the first breeding attempt. Indeed, the three Dutch second broods in produced 13 fledglings, of which one (male) recruit was observed as breeder in (average first year recruitment rate is 4%).…”
Section: Resultsmentioning
confidence: 99%
“…The pied flycatcher is a long‐distance migrant which resides in Europe between April and August (about 5 months), a period used for breeding and moulting. The rest of the year these small insectivorous birds reside in west Africa (about 6 months) or are migrating (about 1 month) (Ouwehand and Both ). Pied flycatchers are most often single brooded, with biparental care.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent meta-analysis, Halupka and Halupka (2017), for example, found that climate change may extend breeding seasons for multibrooded species and reduce it for single-breeding species from the northern hemisphere. We believe that a promising line of investigation would consist in finding other species traits with high capability to predict likely ranges shifts (as forecasted by ENMs).…”
Section: Discussionmentioning
confidence: 99%